Pengaruh Fear Of Missing Out dan Online Customer Experience terhadap Keputusan Pembelian Skincare Scarlett(Studi Pada Generasi Z Pengguna Produk Skincare Scarlett di Yogyakarta) - Alfat Alfat; Heri Prasetyo (MUARA EKONOMI : Jurnal Ilmiah Ilmu Ekonomi, Manajemen & Bisnis, 2026)
This study aims to analyze the influence of Fear of Missing Out (FoMO) and Online Customer Experienceon the Purchasing Decision of Scarlett skincare products among Generation Z in the Special Region of Yogyakarta. The increasing use of social media and the rapid development of e-commerce have changed consumer behavior, particularly among Generation Z, in making skincare purchasing decisions. This study employed a quantitative approach using a survey method. The population consisted of Generation Z consumers in the Special Region of Yogyakarta who had purchased Scarlett skincare products online. The sampling technique used was purposive sampling, with a total of 150 respondents. Data were collected through questionnaires using a five-point Likert scale and analyzed using multiple linear regression analysis with IBM SPSS Statistics version 26. The hypotheses were tested using validity, reliability, classical assumption, t-test, F-test, and coefficient of determination (R²) analyses. The results indicate that Fear of Missing Out (FoMO) has a positive and significant effect on the Purchasing Decision of Scarlett skincare products, with a regression coefficient of 0.483, a t-value of 4.368, and a significance value of 0.000 < 0.05. Online Customer Experiencealso has a positive and significant effect on Purchasing Decision, with a regression coefficient of 0.563, a t-value of 5.901, and a significance value of 0.000 < 0.05. Simultaneously, Fear of Missing Out (FoMO) and Online Customer Experiencehave a positive and significant effect on the Purchasing Decision of Scarlett skincare products among Generation Z in the Special Region of Yogyakarta, as indicated by an F-value of 226.335 and a significance value of 0.000 < 0.05. The Adjusted R Square value of 0.752 indicates that 75.2% of the variance in Purchasing Decision can be explained by Fear of Missing Out (FoMO) and Online Customer Experience, while the remaining 24.8% is explained by other variables not included in this study